The Influence of Social Aspects on Competitiviness of the Inter Organizational Networks: the Experience of the Network of Brazilian Halal Poultry Exporters - de Souza, Leandro Januario; Alssabak, Nawfal Assa Mossa; Macau, Flávio Romero; Carneiro da Cunha, Julio Araujo; Pereira, Cristina Espinheira Costa (Future Studies Research Journal: Trends and Strategies, 2015)
Inter-organizational networks are groups of legally independent organizations working together to achieve both their individual goals to the collective goals of the group. The focus of this research is the influence of social aspects on the competitiveness of inter-organizational networks, and the aim is to identify the contribution of the social aspects (strategy group, trust, commitment and cooperation) to the competitiveness of the network. It is about a qualitative, exploratory and descriptive study, through the case study of a single network of Brazilian poultry exporters of Halal. Primary data were collected through semi-structured interviews, in addition, the information obtained from these interviews were checked with information from other secondary sources such as reports and institutional materials. The results indicated that these social aspects are complementary and collaborate for a more competitive network. The contribution of this research indicates the existence of complementarities of the categories, wherein a positively reinforces the presence of another network.